KINERJA FINANSIAL LEMBAGA KEUANGAN MIKRO AGRIBISNIS DALAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN DI DIY - , ANISA FARDINA RACHMASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research are : (1) to assess financial performance of LKM-A as fund manager of government aids in DIY in the year 2012 and (2) to recognize factors affecting financial performance of LKM-A as fund manager of government aids in DIY . The research was conducted in 30 LKM-As in DIY,using financial ratios including liquidity, solvability and rentability ratios to measure financial performances of LKM-A as fund managers of government aids in DIY. The approaches of this research are using Current Ratio to measure liquidity, ROA, ROE and NPM to measure rentability, as well as DAR and DER to measure solvability. The Ordinary Least Square Methods is also used as statistical method to analyze factors affecting financial performance of LKM-A. The research shows that the financial performance of LKMA in DIY could be categorized as \"safe\" financial institutions indicated by current ratio calculated 44,73% as liquidity ratio, whereas rentability ratio shows ROA (9,51%), ROE (11,95%,) as well as NPM (60,82%). and for solvability ratio shows that DAR (6,39%) as well as DER (12,94%). This research also concludes that at the signifinace level of 0,05%, TATO, DER and LDR have influenced the ROE, whereas the education level of managers has not influenced the ROE.